Inequality and procedural fairness in a money burning and stealing experiment - Zizzo, D (University of Oxford, 2003)
This paper presents the results of an experiment where an unequal wealth distribution was created and then subjects could act to change this wealth distribution. Subjects received money by betting and possibly by arbitrary (undeserved) gifts; they could then pay to reduce, redistribute and, in half of the sessions, steal money from others. The experimental results are incompatible with some standard models of interdependent preferences. Over 80% of redistributors were rank egalitarian, but how subjects perceived the problem significantly affected their redistribution activity: perceptions of fairness were not simply a matter of relative payoff, and changed according to whether a subject was undeservedly advantaged or otherwise.